Key Environmental Factors for Rapid Intensification of the South China Sea Tropical Cyclones - Chen, Yao; Gao, Si; Li, Xun; Shen, Xinyong (Frontiers in Earth Science, 2021)
Forecasting rapid intensification (RI) of the South China Sea (SCS) tropical cyclones (TCs) remains an operational challenge, mainly owing to the incomplete understanding of its physical mechanisms. Based on TC best-track data, atmospheric analysis data, and sea surface temperature data, this study compares temporal evolution characteristics of environmental conditions from the previous 24 h to the onset time for RI and non-RI TCs in the SCS during 2000–2018, and then identifies key factors for RI of the SCS TCs using the box difference index and stepwise regression. A combination of strong divergence in the upper troposphere and strong convergence in the boundary layer, weak deep-layer vertical wind shear, fast storm translation speed, and high TC intensification potential (i.e., maximum potential intensity minus current intensity) north of the storm center at the previous 24 h are favorable for RI of the SCS TCs, and their importance for RI is in descending order. The results may shed light on operational forecasting of rapid intensification of the SCS TCs.